IMPLEMENTATION OF THE QUALITY FAMILY VILLAGE (KB) PROGRAM, LUNAKI MADANI, TO IMPROVE THE QUALITY OF LIFE OF THE COMMUNITY IN KOTO PANJANG VILLAGE, EAST PADANG PANJANG DISTRICT: Implementasi Program Kampung Keluarga Berkualitas (KB) Lembuti Madani Untuk Meningkatkan Kualitas Hidup Masyarakat di Kelurahan Koto Panjang Kecamatan Padang Panjang Timur - Ahmad Lutfi; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the implementation of the Quality Family Village policy in Koto Panjang Village. The background of this study is that the Quality Family Village as a government program to improve the quality of life of the community, the Implementation of the Quality Family Village Policy is a policy that covers a regional unit at the Village level, the Quality Family Village Policy is planned, implemented and evaluated by and for the community. While the central government, local government, non-governmental and private institutions play a role in facilitation, assistance and guidance. In this study, the researcher used a qualitative approach with a descriptive method. The researcher determined the informants through purposive sampling methods and techniques. Data collection was carried out through interviews, observations, and documentation. The validity of the data was tested using triangulation techniques, while data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Quality Family Village program, the mudati madani program, is an effort to improve the welfare of the community in Koto Panjang Village. The Quality Family Village supports a more harmonious family life with adequate facilities, good education, and easier access to health services. And can provide economic opportunities through skills training, small businesses, or even cooperation between families that can increase their income. Overall, Quality Family Villages contribute to more inclusive, empowered and prosperous development.